ABILITY TO WRITE SENTENCES USING ACRONYMS ON JUNIOR HIGH SCHOOL STUDENTS - Etia Sunarsih; Nadir Nur Hajijah (Jurnal Scientia, 2020)
A descriptive study of the ability to write using acronyms is an effort to improve and develop it as a written work using relevant and accountable scientific references. In this study, what was examined was the ability of students in writing sentences using acronyms based on a contextual approach. Frequency calculations are used by calculating the Mean, Mode, and Median and then converting the score into the final value. From the results of this study, it was obtained that the highest score of students in writing sentences using acronyms was 95 classified as excellent criteria, the lowest score in writing sentences using the acronym 75 was classified as right criteria, and the average score of students in writing sentences using acronyms was 89, 06 is classified as an excellent criterion. Then we get a median of 90 and a mode of 90.